Rural development and family agriculture in the Brazilian state of Minas Gerais in the light of multivariate data analysis - Santos, Luana Ferreira dos; Ferreira, Marco Aurélio Marques; Campos, Ana Paula Teixeira de (Interações, 2018)
This paper analyze the rural development in the Brazilian state of Minas Gerais and verify if family farming is a key factor in explaining it. The factor analysis reinforce the importance of the six aspects that influence rural development. The Rural Development Index show that most of the municipalities falls within the category of medium rural development followed by the categories high and low development. The multinomial logit model showed of 45.6% of municipalities, family farming is able to predict the level of rural development.